2001
DOI: 10.1590/s0100-40422001000600024
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre a estrutura atômica superficial e o processo de adsorção-dessorção reversível de hidrogênio em eletrodos monocristalinos Pt(111), Pt(100) e Pt(110)

Abstract: Carlos-USP-CP 780-13560-970-São Carlos-SP Recebido em 1/8/00; aceito em 4/4/01 THE CORRELATION BETWEEN THE ATOMIC SURFACE STRUCTURE AND THE REVERSIBLE ADSORPTION-DESORPTION OF HYDROGEN ON SINGLE CRYSTAL Pt (111), Pt (100) AND Pt (110) ELECTRODES. Platinum is widely used as electrode in electrocatalytic processes, however the use of polycrystalline electrodes introduces a series of variables in the electrochemical system due to the aleatory contribution of all the crystallographic orientations with different su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
2
8
0
6
Order By: Relevance
“…5f, it is clearly observed that the cleavage of ethanol molecule to form adsorbed CO linear occurs on Pt (110) (nonmodified and modified electrode) at lower potentials than on Pt(111) and Pt(100). This could be an influence of the well-known highly stepped (110) face [48]. The intensity of the CO linear band reaches a maximum value at approximately 0.4 V for the intermediary osmium coverage degree studied (θ Os =0.51), different from those observed for Pt(111)/Os and Pt(100)/Os, which show the best performance to form adsorbed CO at lower osmium coverages.…”
Section: Pt(110)/osmentioning
confidence: 67%
See 1 more Smart Citation
“…5f, it is clearly observed that the cleavage of ethanol molecule to form adsorbed CO linear occurs on Pt (110) (nonmodified and modified electrode) at lower potentials than on Pt(111) and Pt(100). This could be an influence of the well-known highly stepped (110) face [48]. The intensity of the CO linear band reaches a maximum value at approximately 0.4 V for the intermediary osmium coverage degree studied (θ Os =0.51), different from those observed for Pt(111)/Os and Pt(100)/Os, which show the best performance to form adsorbed CO at lower osmium coverages.…”
Section: Pt(110)/osmentioning
confidence: 67%
“…1c), the modification by low coverages of Os did not diminish the hydrogen adsorptiondesorption peaks at the 0.1-03 V region, different from the observed behavior for Pt(100) and Pt(111). This feature can be a consequence of the less compact surface structure of Pt (110), the most highly stepped face of platinum [48]. When higher amounts of Os is added to this surface (coverage degree above 0.51), the significant diminishing of the peak at 0.1-03 V is accompanied by a high increase of the current at lower potentials (0.1-0.15 V), which is attributed to a significant increase in the capacitive CV currents.…”
Section: Voltammetric Studiesmentioning
confidence: 99%
“…present in the solution and the adsorbed hydrogen oxidation. In these regions of potential, the superficial arrangement of the atoms is of fundamental importance since they present a different hydrogen adsorption energy and are used to determine the electrochemical active area [20].…”
Section: Resultsmentioning
confidence: 99%
“…5, it is clearly observed that the cleavage of the C-C bond of the ethanol molecule to form adsorbed CO linear occurs on Pt(110) (unmodified and modified electrode) in potentials as low as 0.2 V. This could be an influence of the well-known highly stepped (110) face [28]. The intensity of the CO linear band reaches a maximum value at approximately 0.4 V for a range of osmium coverage degrees between 0.36 and 0.80 ML.…”
Section: In Situ Ftir Studies Of Ethanol and Acetaldehyde Oxidation Omentioning
confidence: 98%